Effect of logging operation on soil carbon storage of a tropical peat swamp forest - Satrio, Anton Eko; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: Since heavy machinery are used in the logging operation activity for extracting the logs on sensitive forest site with peat soil, environment destruction should be the other concern during its processes especially on its important function as soil carbon storage. The objective of this study was to determine whether logging operation affect soil carbon storage of a tropical peat swamp forest. Approach: Soil sampling was conducted before and after logging operation in a 0.3 ha plot to a depth of 15 cm. The soil samples were analyzed for acidity, organic matter content, total carbon, total nitrogen and total phosphorus. The humic acid extraction was also done and soil carbon storage values were obtained by calculation. Paired t-test was used to compare variables under the two treatments (before and after logging) and correlation analysis was used to correlate variables such as soil pH, soil organic matter, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, humic acid yield, unstable carbon and stable carbon. Results: The availability of unstable carbon and stable carbon controlled by soil acidity on undisturbed peat swamp forest as a result, the accumulation of unstable carbon as well as stable carbon occurred even if the soil pH declines and vice versa. However, stable carbon associated well with soil acidity. It was found that the C/P ratio positively correlated with humic acid and stable carbon of both before and after logging conditions. Nevertheless, that association was prominent on logged peat swamp forest. An indication that even though this peat swamp forest had been logged, humification was strongly maintained. However, the similarity of stable carbon of the logged peat swamp forest with stable carbon of undisturbed peat swamp forest indicate an ineffectiveness humification of logged peat swamp forest. Conclusion: Logging operation on sensitive forest with peat soil using heavy machinery increased the bulk density because of compaction. Soil acidity has important role in preserving soil carbon storage of this natural peat swamp forest, especially stable carbon. After the peat swamp forest is logged, humification processes are strongly maintained but slows and becomes ineffective, hence unstable carbon decomposes more instead of it being preserved as stable carbon. Disturbance by logging operation does not alter their amount of soil carbon storage (stable carbon) due to the carbon in humic acid is quite stable within one year.